1447. Molecular Epidemiology, Serotype Distribution, Antimicrobial Sensitivity, and Clinical Findings of adult Pneumococcal Pneumonia Patients in Japan: Hospital-Based Study. (26th November 2018) - Kakiuchi, Satoshi; Suzuki, Motoi; Parry, Christopher M; Yasunami, Michio; Morimoto, Konosuke; ,
Abstract: Background: S. pneumoniae (SP) is one of the most important bacteria for pneumonia among adults. We investigated hospital-based proportion of antimicrobial resistance, distribution of serotypes, sequence types (STs) and clinical findings among adult pneumococcal pneumonia patients, and compared microbiological results with the previous study that was reported 10 years ago in Japan. Methods: A multicenter prospective surveillance for adult pneumonia was conducted from September 2011 to August 2014 in Japan. We enrolled aged over 15 years, community-acquired or healthcare-associated pneumonia patients, and obtained clinical information and sputum samples. Sputum samples were cultured quantitatively or qualitatively at each study sites. Identified SP strains were transported to our laboratory for serotyping by the Quellung reaction. We also extracted DNA from SP strains for multilocus sequence typing. Antimicrobial sensitivity tests for penicillin (PCG), ceftriaxone (CTRX), and meropenem (MEPM) were conducted using agar dilution method. Differences of clinical findings were analyzed using the chi-square test. Results: We enrolled 200 cases and obtained 205 SP strains. Most dominant serotype was three (24.4%) and ST was 180 (22.9%). Those results were same as the previous report. The proportion of 13-valent pneumococcal conjugate vaccine and 23-valent pneumococcal polysaccharide vaccine serotypes was 58.5 and 75.6%, respectively. Most of SP strains were sensitive for antibiotics (96.1% for PCG, 94.1% for CTRX, and 81.5% for MEPM) and the antimicrobial sensitivity also did not greatly have a change with the previous study reported 10 years ago. Pneumococcal pneumonia patients due to serotype 3 was higher hospitalization rate and CURB-65 score than other serotypes (hospitalization rate was 73.5 and 60.3%, respectively; P = 0.095, and proportion of 3 or more CURB-65 score was 36.4 and 20.7%, respectively; P = 0.039). Conclusion: In Japan, SP sensitivity for antibiotics, dominant serotype and ST were not changed so much from 10 years ago. Serotype 3 SP contributed to the disease severity of adult pneumococcal pneumonia in Japan. Disclosures: K. Morimoto, Pfizer: speaker, Speaker honorarium.